PENGARUH PENGUASAAN HUKUM KEKEKALAN ENERGI MEKANIK TERHADAP HASIL BELAJAR FISIKA MATERI POKOK MEKANIKA FLUIDA DI KELAS XI SMA NEGERI PADANGSIDIMPUAN - Mutiara Siagian (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2023)
This study aimed to determine a general idea of mastering the law of conservation of mechanical energy and fluid mechanics, and then I see the influence of the law of conservation of mechanical energy mastery of the learning outcomes of the subject matter of physics of fluid mechanics in class XI of SMAN 8 Padangsidimpuan. The research was conducted using descriptive method.The population is all class XI student are 45 students. The sample is 45 students which are taken by total sampling technique. The data is collected by using test as an instrument. The writer uses statistic processes in analyzing data. They are descriptive analysis and inferential analysis by using the formula of “r” Product Moment and the formula of t test. After collecting the data, it is found the average of mastering the law of conservation of mechanical energy,can be categorized “pretty” .While the average value of the subject matter of physics learning outcomes of fluid mechanics 68.17 can be categorized “pretty”. The result of the analyzed data shows the score of ttest > ttable (2,0 > 1,67) . in other words, the score of ttest is bigger than ttable. So, the hypothesis is accepted. It means there is the influence of the law of conservation of mechanical energy mastery of the learning outcomes of the subject matter of physics of fluid mechanics in class XI of SMAN 8 Padangsidimpuan